Iceland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper estimates the gap between the real effective exchange rate (REER) and its equilibrium (medium-term) value. The paper explores certain features of fiscal policy in Iceland, and examines various aspects of fiscal frameworks in other European countries that are possibly worthy of emulation. It provides a detailed summary of the key issues affecting fiscal policy in Iceland. It argues that political economy factors lead to procyclical fiscal trends, and this is exacerbated by macroeconomic volatility. The paper also provides an overview of the structure of the banking sector of Iceland.